ANALISIS MODEL KURIKULUM PENDIDIKAN AGAMA ISLAM DI ABAD 21 - Zakariyah Zakariyah; Muhamad Arif; Nurotul Faidah (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2022)
The Islamic religious education curriculum model in the 21st century underwent significant changes, especially in the massive 21st century by collaborating between the education curriculum and technology. This fact is based on the many researches that have been published with an emphasis on the Islamic religious education curriculum model. In line with the above situation, the researcher will conduct an in-depth analysis of several research results. The focus of this research problem is how to model the Islamic religious education curriculum in the 21st century. The research uses a qualitative method with a systematic literature review approach. Sources of research data using search results on Google Scholar, Publish and Perlish and Garuda Ristekbrin with a vulnerability of the last 5-7 years with the keywords "Islamic religious education curriculum design", "education curriculum development and design" and "Islamic religious education curriculum in the 21st century" specifically the study criteria selected by the researcher, including; curriculum design, Islamic religious education curriculum design, education curriculum in the 21st century. The results show that some research results of Islamic education curriculum want to give a new color without losing the initial foundation, by designing Islamic religious education curriculum which aims to increase faith and piety to Allah, and make students have a culture of noble character which is collaborated with the development of information technology in the 21st century. Thus, the core design curriculum presented by Murray Print can be a foundation through direct understanding and practice, so that students can absorb lessons optimally. So that the creation of two paths of education, namely vertical (relationship with God) and horizontal path (relationship with humans).